2017
DOI: 10.3390/ijerph14030252
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Distribution of Overweight Adolescents in Immigrant-Rich Areas: Analysis of Disparities among Public and Private School Students in Shanghai, China

Abstract: Accelerated urbanization and rising immigration to the big cities in China has resulted in education policies that produce disparate treatment of immigrant and non-immigrant students. The two types of students frequently wind up in different types of junior high schools. However, there is little research on whether disparities exist between students in public and private schools with regard to overweight. This study aims to address this gap through a comparison of the overweight status of junior high school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[15][16][17] Another study conducted in Shanghai also reported more students at private schools were overweight compared with those at public schools. 18 That study noted that this difference may be explained by diet, socioeconomic status, school environment and factors related to infancy.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 96%
“…[15][16][17] Another study conducted in Shanghai also reported more students at private schools were overweight compared with those at public schools. 18 That study noted that this difference may be explained by diet, socioeconomic status, school environment and factors related to infancy.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 96%
“…The type of school (public, private, or concerted) in which adolescents study and the family´s SES are also related to each other and to the PA levels of the Spanish and Chilean adolescents. This could be due to the fact that, generally, young people with a high family SES reside in environments that promote the practice of PA [ 34 ]. A review carried out on the adolescent population found that young people with a high SES were less likely to be sedentary [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few studies have looked at the impact of school type (public vs private) in China. In general, students who attend feepaying private schools have higher socioeconomic backgrounds than students in public schools (Shi et al, 2017). Private schools usually have smaller class sizes and better teaching resources and facilities which may create a different class culture including peer relationships compared to public schools (Wen et al, 2008).…”
Section: Self-perceived Socioeconomic Status School Type and Gendermentioning
confidence: 99%